METODE KOMUNIKASI INTER PERSONAL PADA PELAYANAN PELANGGAN TERHADAP CITRA PERUSAHAAN LISTRIK NEGARA (PERSERO) RAYON TAKENGON KABUPATEN ACEH TENGAH (Studi deskriptif keluhan tarif listrik di kampung Bebesen) - AB, Subhan; Harahap, Viana Safrida; AK, ALHIDAYATULLAH (Telangke:Jurnal Telangke Ilmu Komunikasi, 2022)
The communication method used by the service officer to the customer is through interpersonal communication. The essence of interpersonal communication is to create, form, or maintain relationships with other peopleThis study aims to determine the Inter-Personal Communication Method in Customer Service Against the Image of the State Electricity Company (Persero) Rayon Takengon Central Aceh Regency (Descriptive Study of Electricity Tariff Complaints in Bebeben Village) and explain the Inhibiting Factors Inter-personal communication methods in customer service to the image of the electricity company state (Persero) rayon Takengon, Central Aceh district (Descriptive study of electricity tariff complaints in Bebeben village)The data collection methods used in this study were interviews, literature study and observation. The data obtained were analyzed qualitatively. Research Results The interpersonal communication method, which is carried out by PLN Rayon Takengon, is very useful, where communication with customers will be easily resolved properly, due to direct face-to-face contact between the community and employees in the complaints faced by the community. Interpersonal communication can unravel customer complaints against PLN services, with interpersonal communication will have a positive impact on the image of PLN itself. By using communication linear communication model, circular communication model, and spiral communication model. So that community response from customers is in the form of direct feedback when two-way or face-to-face communication is running, and indirect feedback. And Interpersonal Communication and Barriers that occur in the communication process include, social status, psychological, socio-cultural, prejudice, semantic barriers and environmental conditions. Providing information, cultivating feelings, and changing attitudes. This is a form of influence from social communication that is conveyed to the community when socializing.